2017
DOI: 10.1149/07801.2045ecst
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of 3-Layer Metal Supported Solid Oxide Fuel Cell Short Stack

Abstract: Metal supported solid oxide fuel cell (SOFC) replaces usual ceramic support with metal for enhancing mechanical strength. Metal supported SOFC has high mechanical strength, better resistance to vibrations and impact than conventional SOFC. In this study, 3-layer metal supported SOFC short stack was designed and developed for auxiliary power unit (APU) application. For the development of metal supported SOFC stack, metal supported SOFC was fabricated by sinter joining process. Electrochemical performance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The uneven temperature distribution is easy to generate thermal stress, which leads to the fracture of the brittle ceramic electrolyte or electrodes, resulting in the degradation of the cell stack [ 140 , 141 , 142 ]. It is widely regarded that the use of metal supports increases the thermal conductivity and the robustness of cell stacks, and the degradation caused by thermal stress has been significantly mitigated [ 29 , 30 , 35 ]. However, no research on the temperature distribution and thermal stress of MSCs stacks has been reported.…”
Section: The Degradation Of Cell Stacksmentioning
confidence: 99%
See 2 more Smart Citations
“…The uneven temperature distribution is easy to generate thermal stress, which leads to the fracture of the brittle ceramic electrolyte or electrodes, resulting in the degradation of the cell stack [ 140 , 141 , 142 ]. It is widely regarded that the use of metal supports increases the thermal conductivity and the robustness of cell stacks, and the degradation caused by thermal stress has been significantly mitigated [ 29 , 30 , 35 ]. However, no research on the temperature distribution and thermal stress of MSCs stacks has been reported.…”
Section: The Degradation Of Cell Stacksmentioning
confidence: 99%
“…Compared with the sealing process of conventional SOCs stacks by using brittle glass-ceramic or mica, the metal welding process can be directly used in the sealing of MSCs stacks [ 9 , 30 ]. Uneven-distributed compressive stress to mica can cause significant gas leakage, which leads to the degradation of the cell stack [ 29 ], while the welding can avoid this risk. Sudireddy et al (2017) [ 30 ] used the laser welding method to seal the MSCs stack with a degradation rate of 0.5–1.2%/100 h (over 2 kh) at 700 °C in moist hydrogen.…”
Section: The Degradation Of Cell Stacksmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal-supported solid oxide fuel cells (MS-SOFCs) can be prepared at lower costs and more compact volumes than traditional ceramics by using inexpensive, strong, and easily processed metals. Due to the good thermal conductivities and mechanical properties of the metal substrate that occupies most of the volume of MS-SOFC, the cell has good thermal shock resistance and excellent quick start ability, reducing the starting time of traditional SOFCs to ten or fewer minutes, accelerating the development of mobile vehicles and other fields [8,9]. This kind of good thermal shock resistance makes MS-SOFC also innovative in operation.…”
Section: Introductionmentioning
confidence: 99%